2016
DOI: 10.1111/jfb.13069
|View full text |Cite
|
Sign up to set email alerts
|

Lateralisation in agonistic encounters: do mirror tests reflect aggressive behaviour? A study on a West African cichlid

Abstract: In this study, population level lateralisation and the suitability of mirror tests as a test of natural aggressive behaviour in male rainbow kribs Pelvicachromis pulcher was investigated. Aggressive behaviour in live agonistic trials correlated positively with behaviours towards a mirror image and no visual lateralisation was detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 25 publications
0
21
2
Order By: Relevance
“…Interestingly, we did not detect a general effect of the opponent's behaviour on the focal fish's behaviour, which is contrary to our previous finding with this same model species of fish (Scherer et al., ). Aggressive behaviour of live stimulus males was relatively similar (i.e.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Interestingly, we did not detect a general effect of the opponent's behaviour on the focal fish's behaviour, which is contrary to our previous finding with this same model species of fish (Scherer et al., ). Aggressive behaviour of live stimulus males was relatively similar (i.e.…”
Section: Discussioncontrasting
confidence: 99%
“…Scherer et al. () have shown that the aggressive behaviour of P. pulcher males covaries positively with an opponent's aggressiveness. Similarly, the difference in activity between live and animation trials could be caused by differences in the activity of live vs. animated opponents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study highlighted the effectiveness of mirror experiments for measuring the intensity of the aggressive behavior in lizards, demonstrating that they do not show self-recognition and attack the mirror image as a true "rival" . Mirror tests have the great advantage of allowing the experimenters to control for the effect of asymmetries in size and residence/motivation, as well as color signal, since each individual can be acclimated in one cage until it becomes resident before facing an intruder having the same size and giving a positive feedback during aggressive contests (Scherer et al 2016). In this study, we used mirrors to assess if aggression varies among morph after removing the main determinants of contest outcome in this species (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…However, the assumption that such mirror tests reliably reflect the true aggressive propensity of an individual have recently been challenged on several grounds: neurobiological studies showed that a mirror images elicit different patterns of gene expression than a live conspecific in the brains of Burton's mouthbrooder ( Astatotilapia burtoni ) (Desjardins & Fernald, ) and zebrafish (Oliveira et al, ). Furthermore, recent studies on different cichlid fishes (e.g., three sympatric lamprologine cichlid species from Lake Tanganyika ( N. pulcher , Lepidiolamprologus elongatus , Telmatochromis vittatus ); two African riverine cichlids ( A. burtoni , Pelvicachromis pulcher ) and South American convict cichlids ( Amatitlania nigrofasciata ) revealed that mirror images elicit meaningful responses only in some of them, but not in others (Balzarini et al, ; Desjardins & Fernald, ; Elwood, Stoilova, McDonnell, Earley, & Arnott, ; Scherer, Buck, & Schuett, ). Thinking about the ways different fish species communicate during aggressive encounters will help explain such contrasting results.…”
Section: Practical and Welfare Aspectsmentioning
confidence: 99%